2020
DOI: 10.3177/jnsv.66.386
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is Associated with Severity of Dry Eye Symptoms and Primary Sjögren’s Syndrome: A Systematic Review and Meta-Analysis

Abstract: We aimed to examine the correlations between vitamin D deficiency, severity of dry eye symptoms and primary Sjögren's syndrome (pSS) by performing a systematic review and meta-analysis. Online databases (PubMed, Cochrane Library, and Embase) were searched to identify controlled studies comparing (1) severity of dry eye symptoms between participants with and without vitamin D deficiency; and (2) serum vitamin D levels between patients with and without pSS. Eighteen studies were included. Overall, individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…The results of the present meta-analysis, based on a statistical analysis of the results of nine studies, show that vitamin D levels are generally lower in SD patients compared with healthy controls, but with a significant overall heterogeneity, indicating several confounding factors. Similar results were observed in the meta-analysis by Kuo et al [ 29 ]. On the other hand, Li et al previously reported comparable serum vitamin D levels between SD patients and controls [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present meta-analysis, based on a statistical analysis of the results of nine studies, show that vitamin D levels are generally lower in SD patients compared with healthy controls, but with a significant overall heterogeneity, indicating several confounding factors. Similar results were observed in the meta-analysis by Kuo et al [ 29 ]. On the other hand, Li et al previously reported comparable serum vitamin D levels between SD patients and controls [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…Vitamin D may intervene in SS pathogenesis, influencing the presence of extra-glandular symptoms such as lymphoma or neuropathy [ 345 ]. One meta-analysis, including 18 studies with SS patients, concluded that patients with vitamin D deficiency associated higher severity scores of dry eye symptoms, such as lower Schirmer’s test scores and higher ocular surface disease index (OSDI) scores [ 214 , 346 ].…”
Section: Vitamin D and Immune-related And Autoimmune Diseasesmentioning
confidence: 99%
“…2023; 3:307 4 inmunitaria y presenta disociación clínica, debido que no se manifiesta clínicamente sino cuando los niveles se encuentran relativamente bajos. (20) Se demuestra que la exposición solar es un factor importante en la presencia de vitamina de D, debido que las exacerbaciones de enfermedades autoinmunes como la esclerosis múltiple se da en primavera, incluso al suplementar vitamina D reduce un 40 % de riesgo; (21) se evidenció el mismo en prevenir el desarrollo de AR. (22,23) Por otra parte, el déficit de vitamina D se asociada a espondiloartopatías, por el contrario, Chen M et al (15) reportaron correlación negativa entre los niveles séricos de Vitamina D y espondiloartopatías.…”
Section: Discussionunclassified